Psychosocial and Socioeconomic Factors in Children with Neurofibromatosis Type 1 - Leppich, Katalin; Schneider, Joanna; Eismann, Caroline; Ryczek, Monika; Potratz, Cornelia; Kaindl, Angela M. (Journal of Pediatric Neurology, 2021)
The aim of this study is to analyze whether children with familial and sporadic neurofibromatosis type 1 (NF1) differ in psychosocial and socioeconomic aspects such as developmental delay as well as in comorbidities. Medical records of 250 children with NF1 at a median age of 10.6 years (range = 2–20 years at time of data collection) were retrospectively reviewed. Specifically, psychosocial and socioeconomic factors from 88 children with a family history for NF1 and 162 sporadic cases were compared. Comparing IQ, familial cases scored significantly lower than sporadic cases (89.8 vs. 96.5; p = 0.015). IQ scores of children with familial and sporadic NF1 differ depending on level of parental education (mean IQ for high education 101.3 [familial] and 102.8 [sporadic] vs. low education 87.5 [familial] and 90.4 [sporadic]; p < 0.001). No significant differences were found regarding the presence of developmental delay, learning disorders, autism spectrum disorder, or attention deficit hyperactivity disease. Children with inherited NF1 had a significantly lower IQ than sporadic cases. Children with familial NF1 more often had parents with a lower level of education, highlighting a possible impact of NF1 through generations. Also, the present study confirmed previous results in literature regarding high frequencies of learning disabilities, autism spectrum disease, and attention deficits in children with NF1.
Keywords: neurofibromatosis type 1; neurofibromatosis; cognition; developmental delays; learning disorders